A further look of the genetic origin and singularity of the Torbiscal Iberian pig line - Carmen Rodríguez-Valdovinos; Juan García-Casco; Fabián García-Ruiz; Yolanda Núñez-Moreno; Luis Silió-López (Spanish Journal of Agricultural Research, 2019)
Although the Torbiscal line of Iberian pigs has been largely studied, some aspects of its history are not well known. In this paper, we used pedigree-based methods on a complete genealogy of 4,077 entries in order to get a comprehensive analysis of its four founder strains and to evaluate the expected genetic contribution of each ancestral strain to the successive generations of the composite Torbiscal line. Between-strain differences and specific heterotic effects on piglet weight at 50 days of age were estimated from records of 9,052 piglets born in 1,571 litters of a complete diallel cross among the four strains. Moreover, we assessed the genetic singularity of the current Torbiscal pigs by other three studies, based on whole genome SNP genotypes, focused on the measure of its genetic diversity and differentiation with respect to other domestic and wild pig populations. The STRUCTURE algorithm detected two uppermost levels of the whole population structure, corresponding to European and Asian ancestries. These results confirmed the exclusive European origin of the Torbiscal and other Iberian pigs and the admixed origin of the Duroc breed. Finally, the comparison of Torbiscal with a representative pool of Iberian pigs showed a maximum genetic differentiation in regions of chromosomes three and seven, including some genes related to the regulation of muscle development.